Date Palm Production Practices and Constraints in the Value Chain in Afar Regional State, Ethiopia - Aregawi Lemlem; Melkamu Alemayehu; Mossa Endris (Advances in Agriculture)
The study was conducted during 2015/2016 in two districts of Afar Regional State which were purposively selected based on their experiences on date palm production and locations relative to Awash River. Objectives of the study were evaluating the existing production practices and constraints of date palm production to generate baseline information for further researches and extension. A total of 117 household heads were interviewed using structured and semistructured questionnaires. Key informant interviews, focus group discussions, and direct observations of date palm plantations have been also conducted. The study was designed to address date palm production along the value chain. The majority of household heads were male, married, and illiterate. About 94.19% of household heads allocated less than one hectare of land for date palm production and had 21–40 years (77.8%) of experience. Seeds (90.6%) were dominantly used for propagation, which are not appropriate for date palm production. Local varieties with low yielding potential were cultivated using flooding irrigation (76.9%). Date palm production was practiced traditionally and constrained with high incidence of insect pests. Capacity building training sessions and researches on proper agronomic, management, and postharvest handling practices are recommended to improve the production of date palm in the region.